Spondyloarthritis, Acute Anterior Uveitis, and Fungi: Updating the Catterall–King Hypothesis - Laurence, Martin; Asquith, Mark; Rosenbaum, James T. (Frontiers in Medicine, 2018)
Spondyloarthritis is a common type of arthritis which affects mostly adults. It consists of idiopathic chronic inflammation of the spine, joints, eyes, skin, gut, and prostate. Inflammation is often asymptomatic, especially in the gut and prostate. The HLA-B*27 allele group, which presents intracellular peptides to CD8+ T cells, is by far the strongest risk factor for spondyloarthritis. The precise mechanisms and antigens remain unknown. In 1959, Catterall and King advanced a novel hypothesis explaining the etiology of spondyloarthritis: an as-yet-unrecognized sexually acquired microbe would be causing all spondyloarthritis types, including acute anterior uveitis. Recent studies suggest an unrecognized sexually acquired fungal infection may be involved in prostate cancer and perhaps multiple sclerosis. This warrants reanalyzing the Catterall–King hypothesis based on the current literature. In the last decade, many links between spondyloarthritis and fungal infections have been found. Antibodies against the fungal cell wall component mannan are elevated in spondyloarthritis. Functional polymorphisms in genes regulating the innate immune response against fungi have been associated with spondyloarthritis (CARD9 and IL23R). Psoriasis and inflammatory bowel disease, two common comorbidities of spondyloarthritis, are both strongly associated with fungi. Evidence reviewed here lends credence to the Catterall–King hypothesis and implicates a common fungal etiology in prostate cancer, benign prostatic hyperplasia, multiple sclerosis, psoriasis, inflammatory bowel disease, and spondyloarthritis. However, the evidence available at this time is insufficient to definitely confirm this hypothesis. Future studies investigating the microbiome in relation to these conditions should screen specimens for fungi in addition to bacteria. Future clinical studies of spondyloarthritis should consider antifungals which are effective in psoriasis and multiple sclerosis, such as dimethyl fumarate and nystatin.